2020
DOI: 10.1186/s40337-020-00316-1
|View full text |Cite
|
Sign up to set email alerts
|

Blind versus open weighing from an eating disorder patient perspective

Abstract: Background: Weighing is a key component in the treatment of eating disorders. Most treatment protocols advocate for open weighing, however, many clinicians choose to use blind weighing, especially during the early phase of treatment. Despite considerable debate about this issue in the literature, there is no empirical evidence supporting the superiority of one weighing approach over the other. In addition, little is known about patients' perspectives of open and blind weighing and which weighing practice they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…For example, open weighing is a component of both CBT (Waller & Mountford, 2015) and FBT (Lock & Le Grange, 2015) for EDs, yet no participant with AN reported experiencing open weighing as part of outpatient therapy. This is consistent with prior research indicating that many providers who treat EDs recommend blind weighing over open weighing, which may be related to beliefs that blind weighing will make the process of weight gain easier (Forbush et al., 2015), patients' preferences for blind weighing (Froreich et al., 2020; Wagner et al., 2022), concerns that blind weighing will reinforce the fear that eating results in rapid weight gain (Murray et al., 2020), and/or therapists' own anxiety about making their patients feel distressed (Levita et al., 2016). In contrast to FBT (Lock & Le Grange, 2015), most participants reported that their parents did not participate in at least 50% of their therapy sessions.…”
Section: Discussionsupporting
confidence: 87%
“…For example, open weighing is a component of both CBT (Waller & Mountford, 2015) and FBT (Lock & Le Grange, 2015) for EDs, yet no participant with AN reported experiencing open weighing as part of outpatient therapy. This is consistent with prior research indicating that many providers who treat EDs recommend blind weighing over open weighing, which may be related to beliefs that blind weighing will make the process of weight gain easier (Forbush et al., 2015), patients' preferences for blind weighing (Froreich et al., 2020; Wagner et al., 2022), concerns that blind weighing will reinforce the fear that eating results in rapid weight gain (Murray et al., 2020), and/or therapists' own anxiety about making their patients feel distressed (Levita et al., 2016). In contrast to FBT (Lock & Le Grange, 2015), most participants reported that their parents did not participate in at least 50% of their therapy sessions.…”
Section: Discussionsupporting
confidence: 87%
“…The second was the omission of regular weighing of the patient in session. Weighing in session is a central key component of most EBI [ 16 ]. The third was the emergence of COVID.…”
Section: Resultsmentioning
confidence: 99%
“…We also noted low levels of in-session weighing. While weighing is a routine practice for EBI in EDs [ 16 ] it is the least endorsed as being received by people describing what occurred when they received cognitive behaviour therapy [ 6 ]. Use of both a bulletin and a workshop on the importance of this weighing supplemented by strategies to manage patient refusal significantly improved occurrence of in-session weighing for face to face appointments, from 48% of sessions to 66.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while at home patients were asked to self‐report their weight. This constant awareness of their own weight, without the support and reassurance of a clinician, may serve to increase anxiety and overconcern with weight (Froreich et al., 2020 ), therefore negatively impacting the ability to restore weight.…”
Section: Discussionmentioning
confidence: 99%